Current Paradigms of Human Resources Management: Leadership and Organizational Climate in Organizations - Bustamante Requena, Jose Luis (2023)
Leadership and organizational climate are crucial concepts in modern-day organizations, irrespective of their size or sector. This study explores the relationship between these concepts in client companies of Tawa Perú S.A. operating in the labor intermediation sector. Using a quantitative approach, the study collected data from 243 employees via a Likert-type questionnaire, thus gaining insights on leadership style and organizational climate. The study’s results demonstrated a strong positive correlation between leadership and organizational climate in the user companies of Tawa Perú S.A., as evidenced by a Spearman correlation coefficient Rho = 0.782. Consequently, both leadership and organizational climate are part of the current paradigm of human resources management, particularly in the labor intermediation sector, whose main function is the delivery of high-quality services with added value to clients. In conclusion, Tawa Perú S.A. and other organizations should prioritize improving the leadership style of their outstanding employees and focus on making them feel comfortable working in the organization through the professionalization of the Employee Care area.